Risk factors associated with herd-level exposure of cattle in Nebraska, North Dakota, and South Dakota to bluetongue virus - Green, Alice L. (2005)
Objective - To evaluate herd-level risk factors for seropositive status of cattle to 1 or more bluetongue viruses. Animals - 110 herds of cattle in Nebraska, North Dakota, and South Dakota. Procedure - Blood samples were collected before and after the vector season. Samples were tested for antibodies against bluetongue virus by use of a commercially available competitive ELISA. Factors evaluated included descriptors of geographic location and management practices. Trapping of insect vectors was conducted to evaluate vector status on a subset of 57 operations. A multivariable logistic regression model was constructed to evaluate associations. Results - For the full data set, altitude and latitude were associated with risk of having seropositive cattle (an increase in altitude was associated with an increase in risk, and a more northerly location was associated with a decrease in risk of a premise having seropositive cattle). Import of cattle from selected states was associated with an increase in risk of having seropositive cattle. From the subset of herds with data on vector trapping, altitude and latitude were associated with risk of having seropositive cattle, similar to that for the full model. However, commingling with cattle from other herds was associated with a decrease in risk of seropositivity. Conclusions and clinical relevance - Findings reported here may be useful in generating additional hypotheses regarding the ecologic characteristics of bluetongue viruses and other vector-borne diseases of livestock. Sentinel surveillance programs are useful for documenting regionalization zones for diseases, which can be beneficial when securing international markets for animals and animal products.